Bia Music: Traditional Music Heritage and Preserving Tradition Across Generations - Kapoyos, Richard Junior; Suharto, Suharto; Syakir, Syakir (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
This research aimed to see the phenomenon of the bia music of the Minahasa tribe that needed to be carefully observed in considering Bia Music then until now was shifting and changing due to the society’s lack of awareness towards Bia Music. This traditional music was very concerning due to the decreasing quantity and quality of the players. The objectives of this research were to analyze: (1) the traditional music heritage and preserving tradition across generations and (2) the educational process in traditional musical performances. The research applied a qualitative method with data collecting techniques by interview, observation, and literature review. Data validation technique based on credibility criteria, using data triangulation. Data analysis techniques consisted of collection, data presentation, data reduction, and data verification. The results of the study show that the younger generation realizes that bia music has become distinctive music that belongs to the community. This music has become part of the social life of the people in Batu village, North Minahasa, so that the educational process in society occurs naturally as a model of inheritance that occurs continuously in society.